242 Is Iliosacral Screw Fixation Safe to Perform in a Day Surgery Unit?. (12th October 2021) - Crawford, P; Brown, C; Jones, B
Abstract: Introduction: Iliosacral screw (ISS) fixation is a percutaneous, fluoroscopy-guided technique which can be used to treat sacroiliac joint pain. During the covid-19 pandemic much of our elective practice has moved from the tertiary referral hospital to the local day surgery unit. We aimed to determine if this procedure is safe to perform as a day case procedure. Method: Twelve patients underwent ISS between 2011-2017: 6 single ISS fixation, 4 two ISS fixation and 2 bilateral ISS fixation. All patients undergoing concurrent procedures were excluded. Mean age 44 years old (range 19-79); 58% male. Surgical time, length of stay, blood transfusion requirement, haemoglobin drop, and significant analgesic events were assessed. Results: Average surgical time was 55 mins (single ISS; range 30-75 mins), 71 mins (two ipsilateral ISS; range 45-100 mins) and 105 mins (bilateral ISS; range 90-120 mins). All patients were discharged within 72 hours; 67% within 24 hours (4 single ISS, 2 two ISS, 2 bilateral ISS). There were no post-operative haemoglobin drops warranting blood transfusion and no delay to discharge due to significant analgesic events. Conclusions: ISS fixation may be safe to perform in a day surgery unit due to acceptable surgical time, length of stay and complication rate. A larger sample size may be required to draw definitive conclusions.